Är reducerad jordbearbetning ett alternativ? - Bäck, Fredrik; Isaksson, Fredrik (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
Today cultivation of cereal in Sweden has high costs for establishment in relation to the rest of the world, and if this cultivation will be able to continue, the farmers have to control their costs. It is important to see all costs, not the maximum harvest achieved, but the net result. All farmers have different conditions with respect to soil, direction of the farm and were the farm is located geographically. With the right knowledge and ambitions, we think most farmers could change to reduced tillage.